Kepuasan Gaji, Kepuasan Kerja, Stress Kerja, Continuance Commitment dan Turnover Intention - Rusmayanthi, Kadek Intan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The purpose of this research is to identify the effect of salary satisfaction, job satisfaction, job stress on continuance commitment and turnover intention. The research was conducted at PT. Telkomsel Regional Bali. Methods of collecting information with a questionnaire to 90 employees of PT. Telkomsel Regional Bali Branch. Information was analyzed by path analysis method with AMOS program. The research results show that salary satisfaction has a negative effect on turnover intention, job satisfaction has a negative effect on turnover intention, job stress has a positive influence on turnover intention, salary satisfaction has a positive influence on continuance commitment, job satisfaction has a positive influence on continuance commitment, job stress has a negative effect on continuance commitment, turnover intention has a negative influence on continuance commitment.